Human Capital Influences Individual Work Performance from Alumni of Vocational High Schools in Telkom Malang - Suryoningtyas, Oktarica Pratiwi (Teknologi dan Kejuruan: Jurnal Teknologi, Kejuruan, dan Pengajarannya, 2021)
The quality of Individual Work Performance (IWP) of workers affects their work productivity in the workplace. This also has an indirect impact on improving the country's economy. The workforce IWP is influenced by human capital. Furthermore, this study was conducted to analyze the human capital of vocational high school graduates on IWP. This study used a survey method with a quantitative approach. The sample of this research was 130 alumni of vocational high school of Telkom Malang in the field of information and communication technology. Human capital indicators were knowledge, competences, skills, and innovativeness. Data collected through surveys and unstructured interviews, then analyzed with descriptive and regression techniques. The findings described respondents’ demographics. Meanwhile, the result of multiple linear regression showed that there was a simultaneous influence between the human capital indicators on the IWP. An effective contribution was determined by IWP’ skill and innovation. To better prepare graduates in their fields, vocational high schools should further increase knowledge, competences, skills, and innovativeness of their students to increase alumni work productivity in the world of work.